A 3D-printed stretchable strain sensor for wind sensing. (21st June 2019) - Al-Rubaiai, Mohammed; Tsuruta, Ryohei; Gandhi, Umesh; Wang, Chuan; Tan, Xiaobo
Abstract: Stretchable strain sensors with large strain range, high sensitivity, and excellent reliability are of great interest to applications in soft robotics, wearable devices, and structure-monitoring systems. Unlike conventional template lithography-based approaches, 3D-printing can be used to fabricate complex devices in a simple and cost-effective manner. In this paper, we report 3D-printed stretchable strain sensors that embed a flexible conductive composite material in a hyper-elastic substrate. Three commercially available conductive filaments are explored, among which the ETPU from Rubber3D Printing, Sweden, shows the highest sensitivity (gauge factor of 20), with a working strain range of 0%–12.5%. The ETPU strain sensor exhibits an interesting behavior where the conductivity increases with the strain. In addition, the resistance change of the ETPU sensor in a doubly-clamped configuration in response to a wind stimulus is characterized, and the sensor shows sensitivity to wind velocity beyond 3.5 m s −1 . The experimentally identified material parameters are used in finite-element modeling and simulation to investigate the behavior of the 3D-printed stretchable strain sensor when subjected to wind loading. In particular, the model-predicted sensor output at different wind speeds, obtained with the computed sensor strain and the experimentally characterized strain-resistance relationship, achieves good match with the experimental data.